Managerial strategies Program addressed to music teachers to stimulate students from 1 to 6 years (Mayéutica Revista Científica de Humanidades y Artes, 2013)
This research was developed from a positivist point of view along with a quantitative approach; it is also a special project. It is supported by a field research, and descriptively, in order to design a managerial strategies program addressed to music teachers to stimulate students belonging to institutes deprived of musical education from Iribarren, Lara state. It was planned in a three stages research: a first stage, a diagnostic of design need. Second stage: a managerial strategies program addressed to teachers was designed. Third stage: a program validation was carried out by experts, considering the results, conclusions and analysis of previous stages. The sample was made up by active teachers during the school period 2012-2013 from nine institutes deprived of music education, located in the municipality Iribarren, Lara state. A Likert instrument for the compilation of information was applied. To analyze the information, descriptive statistics was used using graphical representations. Once the answers obtained were analyzed and interpreted, It was concluded that the teachers present deficiencies and needs when applying managerial strategies, consequently the proposed program is recommended for a better performance as music teachers and managers in the classroom.
Keywords: Managerial strategies; musical stimulation; musical education.